(untitled) (Research, Society and Development, 2022)
The aim of this study was to evaluate the viability of commercial probiotic bacteria (bifidobacteria) in symbiotic beverages made with symbiotic yoghurts and berries pulp, after manufacturing and refrigerated storage. Six beverage formulations were prepared using symbiotic yogurt (60%) containing inulin or fructooligosaccharides (FOS) and commercial probiotic cultures (Bifidobacterium spp.) and berries pulp (40%), as follows: F1 (Howaru HN 019, inulin); F2 (Howaru HN 019, FOS); F3 (Lafti B 94, inulin); F4 (Lafti B 94, FOS); F5 (Kit Bifi, inulin); F6 (Kit Bifi, FOS). The beverages were evaluated for microbiological quality (total and thermotolerant coliforms, molds and yeasts), viability of probiotics, pH and titratable acidity. The pH, acidity and probiotic counts were investigated during 30 days of storage. The physicochemical characterization of the formulations with better performance regarding the maintenance of probiotic counts was carried out. The beverages elaborated showed appropriate sanitary hygienic quality, decreased pH and increased acidity, which is common in fermented dairy products. The probiotic Howaru HN019 exhibited better stability in the beverage than Lafti B4 and Kit Bifi. The highest level of bifidobacteria was found in F1 and F2 beverages containing B. animalis (Howaru HN019) and inulin or FOS, remained around 8 log CFU.mL-1 for up to 30 days, whereas levels of 6 to 7 log CFU.mL-1 were maintained in the other beverages. The beverages made with symbiotic yogurt and berries pulp can be considered an appropriate vehicle for the incorporation of probiotics and fibers, whereas, the probiotics remain at a satisfactory level throughout storage.